2019
DOI: 10.1097/nmd.0000000000001003
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Severity of Symptoms in Croatian Patients With Major Depressive Disorder or Schizophrenia

Abstract: We examined and compared the relationship between religiosity and symptom severity in patients with major depressive disorder (MDD; rated by the Hamilton Depression Rating Scale) and schizophrenia (Positive and Negative Syndrome Scale). Duke University Religion index, Santa Clara Strength of Religious Faith (SCSORF) questionnaire and Brief Religious Coping scale scores were similar between MDD (n=50) and schizophrenia (n=50) patients. In MDD patients, higher organized religious activity (ORA) (estimate=2.28, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…In a longitudinal study, Verghese et al [ 55 ] investigated 323 patients with a diagnosis of schizophrenia and found that an increase in nonpsychotic religious activities predicted a good prognosis in a 2-year follow up. Finally, a Croatian study with 50 psychotic patients[ 56 ] found that higher religious attendance was associated with fewer negative symptoms.…”
Section: Relationship Between S/r and Mental Health Outcomesmentioning
confidence: 99%
“…In a longitudinal study, Verghese et al [ 55 ] investigated 323 patients with a diagnosis of schizophrenia and found that an increase in nonpsychotic religious activities predicted a good prognosis in a 2-year follow up. Finally, a Croatian study with 50 psychotic patients[ 56 ] found that higher religious attendance was associated with fewer negative symptoms.…”
Section: Relationship Between S/r and Mental Health Outcomesmentioning
confidence: 99%
“…Making these accommodations would give providers and patients alike an opportunity to discuss this aspect of the social history towards improving patient quality of life. : Cohen, 2010;Costa, 2022;Erduran-Tekin, 2019;Gearing, 2011;Hook, 2010;Huguelet, 2016;Keri, 2020;Koenig, 2008;Kos, 2019;Lim, 2014;Mohr, 2004Mohr, , 2007Mohr, , 2010aOji, 2010Oji, , 2017Shah, 2011;Smolak, 2013;Triveni, 2017Triveni, , 2021…”
Section: Discussionmentioning
confidence: 99%
“…Незначительные проступки из прошлого получают в сознании больного неоправданное значение, при этом религиозные практики -например, молитва, исповедь, -не приносят никакого облегчения [116]. В исследовании, сравнивающем взаимосвязь религиозности и тяжесть симптомов у пациентов с большим депрессивным расстройством и шизофренией (выраженность религиозности в двух группах была равнозначна по шкалам The Duke University Religion Index [117], the Santa Clara Strength of Religious Faith [118]), было показано, что у депрессивных пациентов с высоко организованной религиозной активностью религиозный копинг чаще является неадаптивным, и, соответственно, тяжесть симптомов выражена сильнее, в то время как у пациентов с шизофренией и расстройствами шизофренического спектра высокоорганизованная религиозная активность коррелирует с меньшей выраженностью негативной симптоматики [119].…”
Section: особенности бредовых расстройств религиозного содержанияunclassified